Supporting Future Cannabis Policy – Developing a Standard Joint Unit: A Brief Back-Casting Exercise - López-Pelayo, Hugo; Matrai, Silvia; Balcells-Olivero, Mercè; Campeny, Eugènia; Braddick, Fleur; Bossong, Matthijs G.; Cruz, Olga S.; Deluca, Paolo; Dom, Geert; Feingold, Daniel; Freeman, Tom P.; Guzman, Pablo; et al. (Frontiers in Psychiatry, 2021)
The standardization of cannabis doses is a priority for research, policy-making, clinical and harm-reduction interventions and consumer security. Scientists have called for standard units of dosing for cannabis, similar to those used for alcohol. A Standard Joint Unit (SJU) would facilitate preventive and intervention models in ways similar to the Standard Drink (SD). Learning from the SD experiences allows researchers to tackle emerging barriers to the SJU by applying modern forecasting methods. During a workshop at the Lisbon Addictions Conference 2019, a back-casting foresight method was used to address challenges and achieve consensus in developing an SJU. Thirty-two professionals from 13 countries and 10 disciplines participated. Descriptive analysis of the workshop was carried out by the organizers and shared with the participants in order to suggest amendments. Several characteristics of the SJU were defined: 1) core values: easy-to use, universal, focused on THC, accurate, and accessible; 2) key challenges: sudden changes in patterns of use, heterogeneity of cannabis compounds as well as in administration routes, variations over time in THC concentrations, and of laws that regulate the legal status of recreational and medical cannabis use); and 3) facilitators: previous experience with standardized measurements, funding opportunities, multi-stakeholder support, high prevalence of cannabis users, and widespread changes in legislation. Participants also identified three initial steps for the implementation of a SJU by 2030: 1) Building a task-force to develop a consensus-based SJU; 2) Expanded available national-level data; 3) Linking SJU consumption to the concept of ‘risky use’, based on evidence of harms.